The Influence of Social Meal BTS Meal Marketing on the Purchase Power of Bandung City Community - Bayu Pamungkas; Muhammad Alwi Alhafidh (Trigin Publisher, 2021)
This research was about conducted with the aim of knowing the people's purchasing power of BTS MEAL in Mc Donald and about the influence of the online management strategy carried out by the company which is Mc Donald. This study uses a quantitative approach with a descriptive method. The sampling method used the saturated sample method, where the entire population was sampled. The number of samples in this study were many respondents. The samples that were observed and studied were consumers who had bought BTS MEAL in Mc Donald and were domiciled and available in Bandung. The correlation coefficient between online marketing strategies and consumer purchasing power of BTS MEAL in Mc Donald shows that this online marketing strategy with consumer buying interest is very effective. It is also supported by data that they know information about BTS Meal in Mc Donald from social media and are interested in buying it because of the very high hype and consider by public interest. The hype makes the reach of BTS Meal's marketing wider and encourages an increase in people's purchasing power. This phenomenon BTS MEAL in Mc Donald all around the world is in line with the syringe theory, where the theory argues that the media can have a great influence on the audience and give the desired effect.